Specificity of the passive hemagglutination test for antibody to rubella virus and the passive hemagglutination response after vaccination. - Cremer, N E (1981)
Nonspecific reactions by the passive hemagglutination test for rubella viral antibody occurred with 1.5% of sera tested. Rises in passive hemagglutination titers (greater than or equal to 4X) occurred with some serum samples taken 14 days after vaccination.